Pre-Stress Linear and Nonlinear Buckling of Cold-Formed Steel Built-up Box Studs - Thu , Ya Mon; Selvam, Janani (International Journal of Sustainable Construction Engineering and Technology, 2023)
In construction industry, cold-formed steel sections become more pertinent in place of hot-rolled steel members. The design guides for CFS are inadequate and hence it is substantial to investigate their governing behaviours as material failure and structural instability (buckling). This study aims to analyse how the buckling behaviours of face-to-face built-up box short columns are administrated by the application of end plates with three different welded spacing. Six geometric models were analysed with ANSYS 2020 R1, numerical software, to evaluate the pre-stress linear and non-linear buckling loads of built-up box studs. The results distinguish the application of end plates and the most effective welded spacing for built-up geometry. It is significant that end plates are more advantageous to resist the maximum compressive loads whereas 509.6 mm is the relevant welded spacing for built-up box section. It is additionally suggested to analyse the governing of weld spacing and end conditions of various built-up geometries: box, sigma and I studs through numerical and experimental analysis.